(untitled) (Al-Farooq Journal of Sciences, 2026)
This study aims to analyze the pivotal role of change management in ensuring the success of digital transformation projects within educational institutions and Libyan university libraries, considering it a fundamental pillar for institutional performance development and the enhancement of academic and research services. The study adopted a descriptive-analytical comparative approach by reviewing global literature and examining modern administrative models (such as Kotter, ADKAR, and the Libyan PACE model), while discussing local challenges related to human resources, infrastructure, and funding. The findings revealed that successful digital transformation requires strategic and conscious leadership, employee engagement throughout the stages of change, and the adoption of a sustainable digital organizational culture. Furthermore, integrating administrative frameworks with open-source technical systems such as Koha ensures flexibility and reduces costs. The study recommends the formulation of national policies for change management and the development of specialized training programs, thereby enhancing the capacity of educational institutions and Libyan university libraries to keep pace with digital advancements and achieve academic and research excellence.